Biopolítica, vida cotidiana e interculturalidad: la clase de inglés como un espacio emancipatorio que da solución al conflicto intercultural bilingüe en un colegio público de Bogotá - Quintana Arias, Ronald Fernando; Bello-Serna, Carol Lizeth (Colombian Applied Linguistics Journal, 2020)
Based on the objective of evidencing the teaching of English as a tool that allows providing a solution to the intercultural bilingual conflict by recognizing the individual and collective local identity of 20 students of a public school in Bogota in 2019, seven sessions are conducted with a case study methodology using a descriptive participatory approach and ethnographic tools which are analyzed under two theoretical categories. The results expose an intercultural bilingual conflict between English-local languages (Spanish-Tikuna), in which the teaching of English has the potential to provide a solution to environmental conflicts and foster other representations of the world. The analysis through the categories of biopolitics and daily life evidenced behavioral micro-revolutions that are born from the interaction of worldviews that generate an intercultural society that revalues the local over the global. It is concluded that, in the context of the research, the English class is an intercultural scenario by nature, which, with teachers who promote the acquisition of intercultural communicative competence, forges interdisciplinarity, generating glocalization through education and curriculum.